PERTANGGUNG JAWABAN KEPALA DAERAH DALAM RANGKA PENYELENGGARAAN URUSAN PEMERINTAHAN - Timumun, Ilyas; Surahman; Asri Lasatu (Universitas Tadulako, 2024)
People's sovereignty in the 1945 Constitution before the Amendment (change) was regulated in article 1 paragraph 2 which states that sovereignty is in the hands of the people and is carried out entirely by the People's Consultative Assembly, the regulation of people's sovereignty in this provision places sovereignty in the hands of the people but its implementation is left entirely to the MPR The third amendment to the 1945 Constitution was the result of the 2001 MPR Annual Session. After the amendment to the 1945 Constitution, article 1 paragraph 2 states that sovereignty is in the hands of the people and is implemented based on the 1945 Constitution, this formulation, if interpreted, means that the highest power is in the hands of the government. or it is based on the will of the people, but the exercise of power is based on the 1945 Constitution, because if people's power is exercised without being based on applicable laws and regulations, it will result in chaotic conditions and threaten the unity and integrity of Indonesia. One aspect of Reform that has received attention Until now it has been a regional autonomy policy issue. Indonesian political perspective After independence in 1945 there were several governments, all of which claimed to be democratic governments. In terms of implementing regional autonomy, regions have rights and obligations which are described in the form of regional income, expenditure and financing which are managed in a regional financial management system efficiently, effectively, transparently, accountably, orderly, fairly, appropriately and in compliance with statutory regulations. -invitation.